Translating metaphors in Chinese satirical literature: a foreignization approach - Tian, Dandan; Redzuan bin Abdullah, Muhammad Alif; Wong, Ling Yann (Bilingual Publishing Group, 2024)
The paper delves into the complexities of translating metaphors in Chinese satirical literature, emphasizing the cultural and linguistic nuances involved. It highlights the importance of metaphors in expressing satire and the challenges posed by cultural differences between Chinese and English. The paper advocates for a foreignization translation approach to preserve the original’s cultural essence and satirical tone, balancing it with explanations to aid understanding in the target language. This method ensures the retention of literary value while facilitating cross-cultural dialogue and appreciation of the source culture’s literary aesthetics.